Controle químico de biótipos de buva (Conyza canadensis e Conyza bonariensis) resistentes ao glyphosate - Yamauti, Micheli Satomi [UNESP] (2010)
Studies were conducted at Estacao Experimental de Citricultura de Bebedouro, SP to evaluate the response of glyphosate-resistant horseweed and hairy fleabane biotypes to herbicides glyphosate, bromacil + diuron, diuron e paraquat isolated and in mixture and effect of a sequential application of glyphosate. The experimental design was of complete randomized blocks with four replication and seven treatments. The herbicides were applied with costal sprayer, constant pressure with three nozzles TT110015, the equivalent spray volume was 150 L ha(-1). The control was visually evaluated, trough percentile note scale. The best results were obtained to general control of weed with diuron isolated and glyphosate in mixture with bromacil + diuron while to glyphosate-resistant horseweed and hairy fleabane there was no difference between the treatments. After sequential application to Conyza sp control, the best treatment was obtained associated with diuron and bromacil+diuron.